Influence of Post-Treatment on the Performances of Plasma Spraying La0.8Sr0.2CrO3 Coating Layer on Ferritic Stainless Steel as Interconnects for Solid Oxide Fuel Cells - Ren, Xiaoqin; Bao, Weitao (Asian Journal of Chemistry, 2014)
The La0.8Sr0.2CrO3 (LSC) coating layer prepared by plasma spraying is an effective means of providing oxidation resistance of ferrite stainless steel as interconnects for solid oxide fuel cells. The results show that a denser coating layer is acquired and the area specific resistances (ASRs) of the LSC coating layer and LSC coating layer modified by post-treatment are 0.18 and 0.015 W cm2, respectively, at 800 ºC after oxidation at 1200 ºC for 20 h, indicating the oxidation resistances of the modified LSC coating layer is significantly improved.